PENERAPAN PELAYANAN PENDAFTARAN PASIEN RAWAT JALAN DI PUSKESMAS - Adawiyah, Robi'atul; Fajarini, Annisa; Husin, Husin (Politeknik Unggulan Kalimantan, 2024)
The outpatient admission place is a health facility at Health Center. The study was conducted to evaluate the implementation of patient registration. There were 3 officers involved, one high school graduate and two medical record graduates. They have attended seminars related to their fields. Although there is a socialized registration SOP, the service is still in the transition process from manual to electronic. Patients must bring their Family Card, BPJS Card, and ID Card to register. Patient data is inputted into the e-health center and evaluated at the end of each month through monthly lokmin meetings